AutoCAD for electrician /c Wan Norhisyam Abd. Rashid Isa, Nik Mohd Zaitul Akmal Mustapha - Wan Norhisyam Abd. Rashid; Nik Mohd Zaitul Akmal Mustapha (Penerbit Universiti Malaysia Pahang, 2012)
This book is focusing on the usage of AutoCAD especially for electrician whereby the contents and knowledge of AutoCAD is described suit for them